Impact of yurt tourism on labor division in nomadic Kazakh families - Talinbayi, S.; Xu, H. G.; Li, W. J. (Journal of Tourism and Cultural Change, 2019)
Tourism’s impacts on ethnic cultures have received much attention, but few studies have been done on its impacts on nomadic people, especially for Kazakh nomads in China. Many Kazakh households are experiencing a transition from pastoralism to tourism, with yurt tourism being the popular Kazakh tourism products. This study takes Narat in China as a case to understand the impact of yurt tourism on the gendered labor division of Kazakh families, and the status of Kazakh women. Observations and semi-structured interviews were adopted. We find that the division of labor in yurt tourism is an extension of traditional nomad labor division and that the traditional gender statuses have been reinforced. Women are required to not only work but also face additional social pressure since they are considered to be going against customary rules when greeting tourists. Despite this, women’s self-confidence, business skills, and income have improved since the development of tourism. We argue that the form of tourism product, ideology of gender roles, and position of ethnic families in the tourism market account for this change. Diverse results of tourism impacts on the gender relationships of ethnic communities can be derived from the interactions of these three factors.